Analisis Pengaruh Manajemen Mutu terhadap Kualitas Layanan dalam Transportasi Gojek - Pradnya Paramitha; Elsha Angelita; Matthew Natanael Riung; Aura Salsabillah Dwi Clandestine (Fakultas Teknik Universitas Maritim AMNI Semarang, 2024)
This article explores the relationship between quality management and service quality at Gojek, a pioneer of online transportation services in Indonesia. Through a quantitative survey, data was collected from 35 Gojek users using an online questionnaire. The analysis results show a positive and significant correlation between quality management and Gojek's service quality. This is evidenced by the majority of respondents expressing their satisfaction with Gojek's services, especially in terms of ease and efficiency, driver friendliness and safety, and practical payment methods. Gojek's success in building a positive brand image and its commitment to meeting user needs also contribute to high service quality.